The Contribution of Pancasila and The Medina Charter Value in Edifying Pesantren - Aminah Aminah (el-Idarah: Jurnal Manajemen Pendidikan Islam, 2019)
The current latent upheaval of national conditions requires Muslims to have a strong foundation and character of movement. Pancasila (the Five Principles) ideology as a pillar of movement characterized by Bhinneka Tunggal Ika (the spirit of unity in diversity), so far has contributed greatly to harmony and peace in the Republic of Indonesia. The nation's independence could not be separated from the sacrifices of the ulamas, the Islamic ummah, the heroes of various religions, and the spirit of patriotism of the Indonesian people at that time. In addition, the majority of Muslims in Indonesia must be a great force in maintaining the integrity of the nation. The method of unifying all the different backgrounds has been exemplified by the figure of Islam, the Prophet Muhammad p.u.b. with the formation of "Baladil Amin" through the Medina Charter By dissecting the essence of Pancasila and the Medina Charter, it is expected that the youth of Indonesian Muslims galvanize themselves earlier, especially in edifying Pesantren. There are two important values that need to be instilled in our Muslim generation, namely universal tawhid (monotheism) and patriotism Universal tawhid is the main thing of religious values, tolerance, moderation and "pluralism". Obviously, this pluralism term is not pluralism understood by liberals, but which is in line with Islamic teachings theologically and practically. While the spirit of patriotism is the value of nationalism that must be built to prepare generations who always love this nation and can adjust themselves to era challenges. The value of universal tawhid and patriotism is expected to be the spirit of the movement of the young generation of Islam especially Santri in fighting for the integrity of the nation and facing the challenges of the times. Moreover they can counteract moral damage, divisions followed by destruction in various segments of nationality caused by the influence of liberalism and radicalism.